2006
DOI: 10.1029/2005ja011257
|View full text |Cite
|
Sign up to set email alerts
|

Dst model for 1995–2002

Abstract: [1] The Dst index is predicted on the basis of the solar wind for the years 1995-2002 using an update of the previous Temerin and Li [2002] prediction model for Dst. The updated model is based on additional data from the years 2000-2002 corresponding to the maximum of the solar cycle and includes several large magnetic storms. For this 8-year period, the linear correlation between the model and the Dst index is 0.956, the prediction efficiency is 0.914, and the RMS error of the prediction is 6.65 nT (nanoTesl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 21 publications
(32 reference statements)
2
148
0
Order By: Relevance
“…60.2 trial and error (Temerin and Li, 2006), which can be found in the study by Boynton et al (2011b). The physical interpretability of the NARMAX algorithm has been used in the past to study the Dst index.…”
Section: The Dst Indexmentioning
confidence: 99%
“…60.2 trial and error (Temerin and Li, 2006), which can be found in the study by Boynton et al (2011b). The physical interpretability of the NARMAX algorithm has been used in the past to study the Dst index.…”
Section: The Dst Indexmentioning
confidence: 99%
“…3). These statistics are common in analysing the performance of models and have been used by Temerin and Li (2006), Li (2004), Boynton et al (2011a) andWei et al (2004a) to name a few.…”
Section: Model Performance Analysismentioning
confidence: 99%
“…Following Burton et al (1975), further corrections and improvements using general relation between the energy balance for the ring current given as the rate of energy input into the ring current and the decay time and DPS relation were done in later studies (e.g., Murayama 1986;Gonzalez et al 1994;Klimas et al 1998;Fenrich and Luhmann 1998;O'Brien and McPherron 2000;Wang et al 2003). The model of this type which is run online in real time is the Dst forecast model by Temerin and Li (2006) at the Laboratory for Atmospheric and Space Physics (LASP, USA) (http://lasp.colorado.edu/space_weather/dsttemerin/dsttemerin.html). The Dst-index is calculated as a sum of several terms Li 2002, 2006).…”
Section: Dst-index As a Storm Indicator Measure And Predictormentioning
confidence: 99%